Analisis Rasio Keuangan Pada PT. Bluebird Tbk Setelah Adanya Sarana Transportasi Berbasis Online - Goni, Marchel R. A.; Tampi, Dolina L.; Manoppo, Wilfried S. (Sam Ratulangi University, 2019)
The purpose of this study was to analyze the Financial Ratio at PT Bluebird Tbk after the existence of online-based transportation facilities. The company's problem arose since the entry of online transportation facilities where there was a significant decrease in income. Ratio analysis in the opinion of Munawir An analytical method to determine the relationship of certain items in the balance sheet or income statement individually or in a combination of the two reports. The research method used is liquidity ratio, solvability ratio and profitability ratio. The results show that the relationship between liquidity and solability can be said to be